Collaborative CSR Frameworks and Volunteer Management Strategies for Mangrove Conservation in Pulau Ketam, Perlis - Sebayang, Saimara A M; Sari, Maya Macia; Faried, Annisa Ilmi; Harun, Nor Harlinda binti; Ulzannah, Nisa (PT. Publikasiku Academic Solution, 2025)
This study focuses on the role of Collaborative Corporate Social Responsibility (CSR) frameworks and volunteer management strategies in mangrove conservation in Pulau Ketam, Perlis. Mangrove ecosystems are vital for coastal protection, biodiversity support, and carbon sequestration. However, these ecosystems face significant threats from human activity and environmental degradation. The study investigates how CSR, combined with effective volunteer management, can provide long-term support for mangrove restoration. A collaborative approach between corporations, government, NGOs, and local communities is essential for creating sustainable environmental programs. The research highlights the importance of volunteer engagement, recruitment, training, and management in enhancing the success of conservation efforts. Findings suggest that CSR frameworks, when integrated with structured volunteer management, improve the sustainability and impact of conservation initiatives. This paper aims to develop a comprehensive model for combining CSR efforts and volunteer management, offering insights into best practices for future conservation projects.